2002
DOI: 10.1046/j.1471-0307.2002.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of white‐brined cheeses: a review

Abstract: White‐brined cheeses are widely produced in the North‐east Mediterranean area and the Balkans. Traditionally, they were manufactured as artisanal cheeses, and nowadays they are manufactured on an industrial scale, and rigorous control of the production and maturation processes is essential. Aspects of the microbiology of white‐brined cheeses and their significance with respect to the quality and safety of the final products are discussed in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 47 publications
(54 reference statements)
4
76
0
1
Order By: Relevance
“…Many yeasts can contribute to taste, flavor, and appearance; however, not all species produce beneficial effects, and a species may benefit one cheese while spoiling another. Particular yeasts on the surface of the cheese can cause spoilage or generate undesirable aromas, flavors, or other metabolic products that reduce the quality of cheese [2,4,23,50]. Furthermore, while yeasts are rarely associated with foodborne infections, studies have shown the presence of medically relevant yeast species in various cheeses, including Candida albicans [11,51], Candida tropicalis [13,51], C. krusei, and C. glabrata [51].…”
Section: Introductionmentioning
confidence: 99%
“…Many yeasts can contribute to taste, flavor, and appearance; however, not all species produce beneficial effects, and a species may benefit one cheese while spoiling another. Particular yeasts on the surface of the cheese can cause spoilage or generate undesirable aromas, flavors, or other metabolic products that reduce the quality of cheese [2,4,23,50]. Furthermore, while yeasts are rarely associated with foodborne infections, studies have shown the presence of medically relevant yeast species in various cheeses, including Candida albicans [11,51], Candida tropicalis [13,51], C. krusei, and C. glabrata [51].…”
Section: Introductionmentioning
confidence: 99%
“…Total anaerobic counts reached 3.08, 2.84, and 3.06 log 10 CFU/g at the end of storage at 5, 15, and 25°C, respectively. A number of species of Bacillus and Clostridium have been reported to thrive under the low pH and high salt content of white-brined cheeses (Bintsis & Papademas 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The consumption of Halloumi has become widespread and the cheese is currently manufactured on an industrial scale in the North East Mediterranean and the Balkans (Bintsis & Papademas 2002). In addition, Halloumi is exported to the European Union and North America to meet the demands of consumers for this cheese (Papademas 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, white-brined cheeses have been manufactured from raw milk and there is a risk that certain pathogens can survive, multiply in restrictive cheese matrix and contaminate the fi nal product [5][6][7]. Furthermore, traditional cheese-making is open to contamination, so there is a growing need to monitor the process hygiene.…”
Section: Introductionmentioning
confidence: 99%